A Novel Local Structure Descriptor for Color Image Retrieval - Zhiyong Zeng (Information, 2016)
A novel local structure descriptor (LSD) for color image retrieval is proposed in this paper. Local structures are defined based on a similarity of edge orientation, and LSD is constructed using the underlying colors in local structures with similar edge direction. LSD can effectively combine color, texture and shape as a whole for image retrieval. LSH integrates the advantages of both statistical and structural texture description methods, and it possesses high indexing capability and low dimensionality. In addition, the proposed feature extraction algorithm does not need to train on a large scale training datasets, and it can extract local structure histogram based on LSD. The experimental results on the Corel image databases show that the descriptor has a better image retrieval performance than other descriptors.